2018
DOI: 10.3390/ma11020327
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Constitutive Model for Predicting Failure of Bulk Metallic Glass Composites Based on the Free-Volume Model

Abstract: A meso-mechanical damage model is developed to predict the tensile damage behaviors of bulk metallic glass composites (BMGCs) toughened by ductile particles. In this model, the deformation behaviors of the BMG matrix and particles are described by the free volume model and Ludwik flow equation, respectively. Weng’s dual-phase method is used to establish the relationship between the constituents and the composite system. The strain-based Weibull probability distribution function and percolation theory are adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Though the performance, productivity and effectiveness of engineering of medical equipment can be assessed using various benchmarks like CE (European Conformity) and others, life cycle prediction data for the majority of medical equipment, including hematology analyzers is currently not available from the manufacturers or the users. Life cycle prediction measures, that provide information on the probability of failure rate of a product, have been utilized in electronic engineering and for dental implants [2,3]. Weibull distribution (2or 3-parameter) is the most representative method that can be used for the modeling of failure rates of mechanical components of a piece of equipment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the performance, productivity and effectiveness of engineering of medical equipment can be assessed using various benchmarks like CE (European Conformity) and others, life cycle prediction data for the majority of medical equipment, including hematology analyzers is currently not available from the manufacturers or the users. Life cycle prediction measures, that provide information on the probability of failure rate of a product, have been utilized in electronic engineering and for dental implants [2,3]. Weibull distribution (2or 3-parameter) is the most representative method that can be used for the modeling of failure rates of mechanical components of a piece of equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Weibull distribution has been studied for deformation behavior of bulk metallic glass composites. Jiang concluded that the statistical model based on Weibull distribution successfully predicted composite yield strength, deformation and elongation [2]. For resin based materials used in computer-aided design and manufacture (CAD/CAM) restorations, Lim et al studied reliability, failure probability and strength and were able to calculate flexural strength of 5% fracture probability [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have been done to identify mechanism of flow stress behavior of MGs under tensile loading and few studies have succeeded to improve tensile flow characteristics in amorphous alloys [6][7][8] . Tensile loading sensitivity is so high that even the MG composites are exposed to the brittle fracture 9,10 . Moreover, high temperature flow mechanism of MGs can be a turning point for deep understanding of their plasticity in various conditions [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%